NK cells are activated and primed for skin-homing during acute dengue virus infection in humans - Christine L. Zimmer; Martin Cornillet; Carles Solà-Riera; Ka-Wai Cheung; Martin A. Ivarsson; Mei Qiu Lim; Nicole Marquardt; Yee-Sin Leo; David Chien Lye; Jonas Klingström; Paul A. MacAry; Hans-Gustaf Ljunggren; et al. (Nature Communications, 2019)
Here, Zimmer et al. analyze the natural killer (NK) cell response in a patient cohort with acute dengue virus infection showing early NK cell activation and proliferation, and the data suggest that NK cell proliferation depends on IL-18 signaling, and that responding NK cells have a skin-homing phenotype.